THU0451 Comparing Four Screening Tools for Psoriatic Arthritis among Subjects Diagnosed with Psoriasis. (15th July 2016) - Baddoura, R.M.; Tomb, R.; Ghanem, A.; Halaby, E.; Mansour, N.; Ayoub, N.; Stephan, F.; Soutou, B.; El Sayed, F.; Ammoury, A.; Megarbane, H.; Helou, J.
Abstract : Background: Screening psoriatic arthritis remains a challenge. A few dedicated tools have been developed in different settings however direct comparative data is limited. Objectives: To compare screening properties of a new instrument [PsoQ], inspired by both ASAS recommendations for early diagnosis of spondyloarthritis and ACR criteria for rheumatoid arthritis, to three others developed in the setting of dermatology practice [PAQ, PASE and PEST]. Methods: Consecutive subjects diagnosed with psoriasis by the dermatologist were submitted the four questionnaires. Subjects with scores above the reported threshold values and a set value for the new instrument, designated as screened positive, were offered rheumatological assessment to search for psoriatic arthritis. Screening properties of the four tools were compared. Results: 371 patients with a mean (SD) age of 39.1 (16.9) were included [204 women (54.9%)]. Predominant psoriasis phenotype was psoriasis vulgaris (78%); prevalence of nail involvement was 15.6% and of scalp lesions 33.7%. 103 patients (27.0%) were screened positive using either of the four questionnaires: 25 (6.8%) using the PAQ questionnaire, 55 (14.8%) with the PASE questionnaire and 41 (11.1%) by the PEST questionnaire. 52 (14.0%) reported features of inflammatory back pain and 32 (8.6%) reported features of inflammatory peripheral arthritis and accordingly 68 (18.3%) were screened positive by the PsoQ. In total, 10 patients were identified as psoriatic arthritis (prevalence 2.7% (95%CI: 1.1%; 4.3%). Predominantly axial phenotype was present in 5 subjects and peripheral arthritis phenotype in five. Sensitivities (SE) and specificities (SP) of the four questionnaires ranged between 70% and 100% for SE and between 83.9% and 94.4% for SP. SE was the highest using PsoQ (100%) while SP was the highest using PAQ7 (94.4%). Positive predictive values (PPV) were low, between 12.7% and 20.0% while negative predictive values (NPV) were high, between 98.6% and 100.0%. The highest PPV was achieved with PAQ7 (20%) and the highest NPV (100%) was obtained with PsoQ. Positive likelihood ratios (PLR) were moderate ranging from 5.3 to 8.8 and negative likelihood ratios (NLR) ranged between 1.9 and 4.5. Conclusions: The four tools showed similar screening properties. Subjects with scores above threshold values need referral for rheumatological assessment. References: Limitations in Screening Instruments for Psoriatic Arthritis: A Comparison of Instruments in Patients with Psoriasis. Walsh JA. et al. J Rheumatol 2013;40:287–93 Disease assessment in psoriatic spectrum: a modular approach for use in routine clinical practice. Wajed J. et al. Ann Rheum Dis 2013;0:1–2. Acknowledgement: St Joseph University Council for scientific research for main funding of the study Abbvie pharmaceuticals for partial funding of the study Disclosure of Interest: None declared